Little White Duck : A Childhood in China - Na Liu (Minneapolis, United States Lerner Publishing Group, 2013)
A young girl describes her experiences growing up in China, beginning with the death of Chairman Mao in 1976.
Keywords: Gender Equality; Biographies / Autobiographies